Role of pelvic packing in the first attention given to hemodynamically unstable pelvic fracture patients: a meta-analysis - Pengyu Li; Fanxiao Liu; Qinghu Li; Dongsheng Zhou; Jinlei Dong; Dawei Wang (Journal of Orthopaedics and Traumatology, 2022)
Abstract Purpose To evaluate the effectiveness of pelvic packing (PP) in pelvic fracture patients with hemodynamic instability. Materials and methods Three databases—PubMed, Embase and the Cochrane Library—were systematically searched to identify studies presenting comparisons between a protocol including PP and a protocol without PP. Mortality, transfusion requirement and length of hospitalization were extracted and pooled for meta-analysis. Relative risk (RR) and standard mean difference (SMD), along with their confidence intervals (CIs), were used as the pooled statistical indices. Results Eight studies involving 480 patients were identified as being eligible for meta-analysis. PP usage was associated with significantly reduced overall mortality (RR = 0.61, 95% CI = 0.47–0.79, p < 0.01) as well as reduced mortality within 24 h after admission (RR = 0.42, 95% CI = 0.26–0.69, p < 0.01) and due to hemorrhage (RR = 0.26, 95% CI = 0.14–0.50, p < 0.01). The usage of PP also decreased the need for pre-operative transfusion (SMD = − 0.44, 95% CI = − 0.69 to − 0.18, p < 0.01), but had no influence on total transfusion during the first 24 h after admission (SMD = 0.05, 95% CI = − 0.43–0.54, p = 0.83) and length of hospitalization (ICU stay and total stay). Conclusions This meta-analysis indicates that a treatment protocol including PP could reduce mortality and transfusion requirement before intervention in pelvic fracture patients with hemodynamic instability vs. angiography and embolization. This latter technique could be used as a feasible and complementary technique afterwards. Level of evidence 3.